최고경영자의 리더십 탈락(derailment)에 관한 고찰 - 이기은(Kieun Lee) (대한경영학회지, 2021)
리더십은 오랫동안 관심을 받아온 주제인데, 관심의 대부분은 긍정적인 성공적인 리더십에 놓여 있었다. 리더십의 성공으로 인해 조직에 큰 좋은 영향을 미칠 수도 있지만 상대적으로 리더십 실패로 인한 부정적인 영향과 리더십의 어두운 측면에 대해서는 관심이 상대적으로 소홀하였다. 본 연구에서는 리더십 실패의 한 가지 유형인 리더십 탈락에 대해 살펴보고자 한다. Shackleton(1995)에 따르면, 리더십 탈락은 리더가 조직내에서 높은 수준에 이르렀으나 조직에서 기대했던 것만큼 높이 올라가지 못하고 경력이 정체되거나 강등되거나 해고되거나 조직퇴직되거나 권한이 축소된다. 리더십 탈락의 원인에 관한 연구들을 여러 유형으로 구분되었다. 첫째, 리더의 성향에 초점을 맞춘 연구로서 탈락과 연결될 수 있는 나르시시즘과 같은 부정적인 성향들과 탈락과의 관계를 살펴본 연구이다. 둘째는, 리더십 또는 관리리적인 기술이나 능력에 초점에 맞춘 연구이다. 대인관계 기술, 사업관련 기술, 팀 구축관련 기술, 새로운 변화에 적응하는 것과 관련된 변화관리 기술 등이 많이 언급되었다. 셋째, 상황의 변화에 관한 것이다. 시간이 변화하면서 과거에는 중요하지 않았던 사항이 중요하게 등장하게 되었으며 과거에는 리더에게 강점이었는데 후일에는 약점으로 변화되는 것에 관한 연구가 있었다. 그리고 시간의 흐름에 따라 나타나는 리더십 탈락의 단계와 과정에 관한 연구들이 있었다. 넷째, 리더의 성공으로 발생되는 실패에 관한 연구이다. 이카루스의 역설과 성공의 역설은 과거 성공의 수단이었던 것에 지나치게 의존하게 되어 이것이 오히려 실패를 가져오게 되는 경우이다. 경영자의 휴브리스는 경영자가 과거의 성공으로 인해 지나치게 과신하게 되는 현상이 다. 밧세바 증후군은 성공한 사람이 권력을 부정하게 사용하여 도덕적으로 잘못된 행동을 연속적으로 행하는 잘못에 관한 것이다. 도덕적 허가는 도덕적 행위를 하는 사람이 왜 비도덕적 행위를 하는 현상을 설명한다. 리더십 탈락에 대한 대안으로는 조직차원과 개인차원으로 나누어 제시하였다. 조직차원에서 신중한 선발을 통하여 리더의 탈락을 줄여야 하며, 개발분야에서는 자기인식 향상 방법, 리더십 기술 향상 방법, 경력경로의 확대, 변화에의 적응관리 방법 등을 제시하였다. 개인차원으로는 적극적인 경청, 적극적인 학습, 진성리더와균형잡힌 삶 등을 제시하였다. 마지막으로 연구의 기여점과 연구의 한계 및 향후 연구방향을 제시하였다. Leadership has been one of the most popular topics studied in organization literature for very long time. The focus of leadership research has leaned toward such positive and constructive issues as leadership effectiveness, identifying the traits and skills of successful leaders, effective leadership theories, and leadership development programs. But although in reality more leaders fail than succeed, very little interest has been given about negative destructive subjects like leadership failure. The purposes of this study are to review why leaders fail, to categorize the researches on leadership derailment and to provide what to do for the prevention of derailment. Leadership derailment is a part of leadership failure. According to Shackleton(1995), derailed leaders have achieved a very high level but did not go as high as the organization had expected and may have been involuntarily plateaued, demoted or fired, accepted early retirement, or had responsibilities reduced below the level of expected achievement. The researches on leadership derailment were categorized into the causes of leadership derailment. First, there has been many studies focused on leader's personal dispositions. Some studies indicate that derailed leaders lack certain positive traits like emotional stability and integrity or have negative tendencies or personalities like narcissim and arrogance. Second, some studies have compared the successful leaders with the derailed to try to find what the derailment factors were. The common derailment factors shown in many studies were underdeveloped leadership skills or competencies; problems with interpersonal relationships, failure to meet business objectives, inability to build and lead a team, and inability to change or adapt during a transition. Third, the changes of situation may give rise to make successful leaders the derailed. The strengths and personal dispositions that get people promoted to higher positions can become weaknesses or flaws that lead to derail them. The weaknesses which did not matter previously or which were forgiven due to in good performances may become more obvious in a new position. For exemple, if a manager at low level is very smart technically, his or her insensitivity can be tolerated. But at higher level the excellent technical competence is no compensation for abrasiveness. Some studies showed the derailment stages and processes. Finally, leadership derailment can be caused by success of leader. 1) In Greek myth, Icarus died after flying too near the sun on wings made of feathers and wax. According to Miller(1992), the Icarus paradox is that his greatest asset led to his demise. Success or good results may seduce leaders into the excesses and complacency that cause their downfall. 2) According to Hayward and Hambrick(1997), hubris, which is caused by recent organizational success, media praise for the CEO, and CEO's self-importance, involves exaggerated pride or self-confidence, often resulting in retribution. Many studies have focused on CEO hubris, as CEOs' overconfidence in business, and its dertimental effects on corporates. 3) The story of King David and Bathsheba is in the Old Testament. Ludwign and Longenecker(1993) suggested that many ethical violation by upper managers were the by-product of success, not of competitive pressures. Bathsheba syndrome refers the ethical failure of successful leaders. 4) Moral licensing explains why people who have behaved in a moral way in the past are likey to display immoral, unethical, or problematic behaviors. The measures to prevent leadership derailment are suggested. In organizational level, the number of derailers can be reduced with careful selection efforts and with effective development programs to help leaders enhance self-awareness, improve leadership skills, enlarge career path, and adapt the transition. In individual level, leaders try to be active listeners to get honest useful feedback, to be active learners to impo... KCI Citation Count: 0